Transcranial optogenetic brain modulator for precise bimodal neuromodulation in multiple brain regions - Hyogeun Shin; Min-Ho Nam; Seung Eun Lee; Soo Hyun Yang; Esther Yang; Jin Taek Jung; Hyun Kim; Jiwan Woo; Yakdol Cho; Youngsam Yoon; Il-Joo Cho (Nature Communications)
Abstract Transcranial brain stimulation is a promising technology for safe modulation of brain function without invasive procedures. Recent advances in transcranial optogenetic techniques with external light sources, using upconversion particles and highly sensitive opsins, have shown promise for precise neuromodulation with improved spatial resolution in deeper brain regions. However, these methods have not yet been used to selectively excite or inhibit specific neural populations in multiple brain regions. In this study, we created a wireless transcranial optogenetic brain modulator that combines highly sensitive opsins and upconversion particles and allows for precise bimodal neuromodulation of multiple brain regions without optical crosstalk. We demonstrate the feasibility of our approach in freely behaving mice. Furthermore, we demonstrate its usefulness in studies of complex behaviors and brain dysfunction by controlling extorting behavior in mice in food competition tests and alleviating the symptoms of Parkinson’s disease. Our approach has potential applications in the study of neural circuits and development of treatments for various brain disorders.